Genome and transcriptome analysis of Enterococcus faecium from intestinal colonization and Enterococcus faecium from urinary tract infection - Huang, Ge; Zhou, Yizheng; Cheng, Hai; Lv, Tao; Zheng, Lisi; Li, Chengbin; Chen, Yunbo (Frontiers in Microbiology, 2023)
Introduction: Enterococcus faecium is a common pathogen responsible for urinary tract infections (UTIs) and often establishes extensive colonization within the intestinal tract. Our aim was to assess the genomic and transcriptomic differences between colonized E. faecium without UTI (only-colonization) and colonized E. faecium causing UTI (endogenous infections).We investigated the correlation between fecal isolates from the same patient and UTI-causing isolates using PFGE and WGS, and classified fecal isolates into two groups: those that solely colonized and those associated with endogenous urinary tract infections. We characterized the genomes of colonization-only and endogenously infected isolates by Scoary GWAS, and the transcriptomes of the isolates at 3-h urine exposure to assess pathogen-related changes.Result: Based on PFGE and WGS, eight isolates of endogenously infected E. faecium and nine isolates of only-colonized E. faecium were characterized and carbon and nitrogen regulated metabolisms such as genes encoding the phosphotransferase (PTS) system were enriched in endogenously infected E. faecium. Transcriptome analysis revealed significant differences in gene expression in the PTS system, lysine synthesis, galactose metabolism and citrate import between endogenously infected and only-colonized E. faecium isolates, highlighting the important role of certain carbon regulatory genes in the colonization and survival of endogenously infected E. faecium.In only-colonized and endogenously infected isolates, we observed differential expression patterns of genes related to carbon metabolism and amino acids, suggesting that metabolic diversity is a strategy for isolates leading to endogenous infection.